2009
DOI: 10.1158/0008-5472.sabcs-09-5013
|View full text |Cite
|
Sign up to set email alerts
|

Greater Anti-Angiogenic Effects with Docetaxel Compared with Anthracyclines in the Neoadjuvant Treatment of Breast Cancer.

Abstract: Background: Dynamic contrast-enhanced MRI (DCE-MRI) allows for the functional assessment of tumour permeability and perfusion and has been previously shown to predict for clinical and pathologic response in women with breast cancer undergoing neoadjuvant anthracycline based chemotherapy1. Changes in DCE-MRI kinetic parameters after 2 cycles of neoadjuvant chemotherapy (NAC) predicts clinical and pathological benefit, with transfer constant Ktrans being the best predictive biomarker. This study examines (1) whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Neoadjuvant chemotherapy regimens used in the treatment of breast cancer commonly consist of an anthracycline in combination or sequentially administered with taxanes. The mechanism of action of anthracyclines is mainly attributed to the inhibition of DNA synthesis, preventing the replication of rapidly dividing cells [ 34 ] , whereas taxanes have been reported to have an anti-angiogenic effect with selective shutdown of microvessel formation [ 35 , 36 ]. This is supported by the significant increase in DDC seen on mid-treatment ( p = 0.04), suggesting a change in the distribution of diffusion compartments resulting from the early breakdown of the vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant chemotherapy regimens used in the treatment of breast cancer commonly consist of an anthracycline in combination or sequentially administered with taxanes. The mechanism of action of anthracyclines is mainly attributed to the inhibition of DNA synthesis, preventing the replication of rapidly dividing cells [ 34 ] , whereas taxanes have been reported to have an anti-angiogenic effect with selective shutdown of microvessel formation [ 35 , 36 ]. This is supported by the significant increase in DDC seen on mid-treatment ( p = 0.04), suggesting a change in the distribution of diffusion compartments resulting from the early breakdown of the vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Salhotra et al (9) attributed this to an increase in cellular proliferation and subsequent accumulation of defective proteins. Application in human brain cancer has further indicated the sensitivity of CEST MRI, particularly APT, for the delineation of neoplasia in vivo (5, 10, 34, 35). Treatment effects have been explored by Zhou et al using a radiation necrosis model in rats (10), demonstrating the ability to detect viable malignancy from radiation necrosis and predicting tumor response to targeted radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the peak pulse amplitude was swept between 0.25 and 1.25 μT in increments of 0.25 μT, whereas the number of pulse elements and duty cycle were held constant at 35 and 90%, respectively. In addition, the effects of duty cycle were examined at values of 50%, 60%, 70%, and 80% with the number of pulses per pulse repetition time (35) and pulse duration (25 ms) held constant. Finally, the total duration of saturation was examined at 440, 600, and 907 ms, both while holding the peak pulse amplitude (0.5 μT) and pulse duration (25 ms) constant.…”
Section: Methodsmentioning
confidence: 99%
“…Taxanes have been reported to have greater antiangiogenic activity compared to anthracyclines, and selectivity for the inhibition of endothelial cell migration and/or microvessel formation . In our study, significant differences were found in the early reduction of the VMs of the patients with LABC between those treated with taxane‐containing regimens and those treated with regimens not containing taxanes, consistent with the prior observation.…”
Section: Discussionmentioning
confidence: 99%
“…The neoadjuvant chemotherapy regimens were mainly anthracycline or taxane‐based, and a few patients received vinorelbine or cisplatin‐based chemotherapy regimens. Taxanes have been reported to have greater antiangiogenic activity compared to anthracyclines in the neoadjuvant treatment of breast cancer, and preclinical studies have reported that taxanes have strong antiangiogenic activity via inhibition of the proliferation and differentiation of the endothelial cells . Therefore, the treatment response between the patients receiving regimens containing and not containing taxanes was also evaluated separately.…”
Section: Methodsmentioning
confidence: 99%